Immune checkpoint inhibitors plus chemotherapy in the first-line treatment of young unresectable gastric cancer patients: a multicentre real-world study - Wang, Yingnan; Li, Yan; Liu, Zheng; Liu, Jing; Xu, Hongmei; Zhang, Ruixing; Zhang, Fengbin; Guo, Zhanjun (Frontiers in Oncology, 2025)
BackgroundPD-1 inhibitors combined with chemotherapy have become the standard first-line treatment for advanced gastric cancer (GC), but their efficacy in young GC patients is unknown. This study aimed to evaluate the efficacy of immunotherapy in young GC patients and explore new treatment strategies for this population.MethodsClinicopathological data of young unresectable GC patients were collected from multiple centres. We defined young as ≤45 years. Statistical analyses were conducted with SPSS IBM for Windows version 24.0.ResultsIn total, 225 young unresectable GC patients were registered. Their clinicodemographic characteristics included female predominance (60.9%), poor differentiation (86.7%), high family history of cancer (14.2%), low HER2 expression (12.2%), PD-L1 expression (43.0%) and mismatch repair (MMR) deficiency (1.0%), and a high proportion of peritoneal metastasis (49.3%). After screening, 134 patients were included for analysis: 63 received dual chemotherapy (mFOLFOX6, XELOX, SOX and two-drug containing paclitaxel), 32 PD-1 inhibitors plus dual chemotherapy (mFOLFOX6, XELOX, SOX and two-drug containing paclitaxel), and 39 triple regimens (two-drug chemotherapy combined with apatinib or trastuzumab, or triple chemotherapy based on platinum, fluorouracil and paclitaxel). The effectiveness analysis revealed no significant difference in the disease control rate (DCR) between the dual chemotherapy group and the PD-1 inhibitor plus dual chemotherapy group (P=0.787), but triple regimens led to the best DCR (71.4% vs. 68.8% vs. 94.9%, all P<0.05). Kaplan–Meier curves showed median progression-free survival (PFS) times of the three groups of 4.7, 4.7 and 9.2 months, respectively. The median overall survival (OS) was 13.9, 11.0 and 15.9 months, respectively. Multivariate analyses showed that triple regimens were an independent prognostic factor for PFS [hazard ratio (HR) 0.430, 95% confidence interval (CI) 0.263-0.700; P=0.001]. Detailed survival analysis demonstrated that patients receiving intraperitoneal infusion of paclitaxel followed by intravenous paclitaxel combined with S-1 and apatinib oral therapy had better PFS (P=0.014) and OS (P=0.013) than those receiving other regimens.ConclusionYoung patients with GC have unique clinical characteristics and are not sensitive to immunotherapy. Triple regimens, especially intraperitoneal infusion of paclitaxel followed by intravenous paclitaxel combined with S-1 and apatinib oral therapy, deserve to be studied as first-line therapies.